New-generation trade agreement with Japan: Significance to EU Companies - Małgorzata Czermińska (International Entrepreneurship Review, 2022)
Objective: The New-generation trade agreements, which include the agreement with Japan, provide wide coverage – not only the liberalisation of trade in goods or services but also the protection of intellectual property rights, the public procurement market, sustainable development and others. This paper aims to demonstrate key provisions and (both ex post and ex ante) opportunities that the agreement creates for EU companies.